INFLUENCE SOCIAL MEDIA MARKETING AND BRAND AWARENESS REGARDING THE DECISION TO PURCHASE BEAUTY PRODUCTS SOMETHINC IN SURABAYA - Adviola, Tiara Febry; Aminah, Siti (Yayasan Education and Social Center, 2024)
This research study set out to examine the influence of social media marketing and brand awareness on the purchase decisions of Somethinc products among residents of Surabaya. The target population for the investigation consisted of Surabaya residents who had previously purchased and used Somethinc products. A non-probability sampling approach with purposive sampling was employed to obtain a sample size of 91 participants. Data was collected via a survey method using a questionnaire with a Likert scale. The analysis utilized path analysis with Partial Least Squares (PLS) to evaluate the data. The results demonstrate that both social media marketing and brand awareness have a significant positive effect on the purchase decisions of Somethinc beauty products within the Surabaya market.